The Schrödinger's Cat of Gang Groups: Can Street Gangs Inform Our Comprehension of Skinheads and Alt-Right Groups?. Issue 10 (3rd October 2019) - Valasik, Matthew; Reid, Shannon E.
ABSTRACT: Given the current political climate, the mainstreaming of Alt-Right groups, and growing public concern, this paper argues that gang scholars are well situated to investigate these Alt-Right groups and their members. Qualitative and quantitative data collected from youth incarcerated within California's Division of Juvenile Justice are used to examine the differences and similarities between a range of individual-level risk factors and group-level descriptors to better understand the overlap between members of racist skinhead/Alt-Right groups and street gangs. Findings highlight how closely aligned these two groups are across domains.